2023
DOI: 10.1039/d2ra07498b
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and anion sensing properties of a triphenylamine–dioxaborinine trimeric compound

Abstract: The one-pot triphenylamine functionalization with multiple dioxaborinine groups gives the novel dye A2 with two-photon absorption and cyanide-sensing properties. The solvatofluorochromism of A2 was interpreted in terms of solvent dipolarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Remember that fluorophores containing dioxaborinine core have been widely reported; [5–12,26,32–34] nevertheless, those bearing the pyrazolo[1,5‐ a ]pyrimidine ring are rare, although some interesting examples have been reported in our research group [16,17,22,29,35,36] . Fluorophores of extended π‐conjugation ( Py‐DB , R 2 ‐DB , and TPA‐DB 3 ) and with various substitutions such as phenyl ( Ph 2 ‐DB ), methoxyaryl ( Py‐DB , R 2 ‐DB , and Ar‐PP ), TPA ( TPA‐DB , TPA‐DB 3 , and TPA‐PP ), and coumarin ( Cum‐DB ) groups were used in this analysis.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Remember that fluorophores containing dioxaborinine core have been widely reported; [5–12,26,32–34] nevertheless, those bearing the pyrazolo[1,5‐ a ]pyrimidine ring are rare, although some interesting examples have been reported in our research group [16,17,22,29,35,36] . Fluorophores of extended π‐conjugation ( Py‐DB , R 2 ‐DB , and TPA‐DB 3 ) and with various substitutions such as phenyl ( Ph 2 ‐DB ), methoxyaryl ( Py‐DB , R 2 ‐DB , and Ar‐PP ), TPA ( TPA‐DB , TPA‐DB 3 , and TPA‐PP ), and coumarin ( Cum‐DB ) groups were used in this analysis.…”
Section: Resultsmentioning
confidence: 96%
“…498/532 98500 1300 65 DCM [À À ], Suhasini et al [30] 430/527 -4300 49 DMF [À À ], Haucke et al [34] 366/397 40700 2100 39 Toluene [20], Yang et al [32] 379/468 18000 5000 77 CyH [3], Tigreros et al [35] 502/570 129000 2400 61 DCM [1], Chaicham et al [33] 353/479 5100 7500 44 DCM [10], Castillo et al [36] 449/531 87100 3300 85 CHCl 3 [10], Tigreros et al [12] 347/477 17700 7900 69 THF [20], This work 386/454 40700 3900 93 DMSO [20], Wang et al [26] [a] If no information is reported by the authors in the respective work, we assume that such dyes are obtained starting from commercial substrates. distribution throughout the molecule due to the high πconjugation in this compound (Figure 2a).…”
Section: Computational Calculationmentioning
confidence: 99%
See 3 more Smart Citations